The Inverse Perspective in Byzantine Painting - Maria Urmă (Anastasis: Research in Medieval Culture and Art)
The inverse perspective is a method of representing spatial depth used only in Byzantine painting. It is different from Renaissance perspective (a method of realistic, conventional, subjective, subject to a single point of view). The inverse perspective, with two-dimensional axonometric representations, is more complex, offering multiple possibilities of symbolization. Various theories have considered either optical-geometric aspect or artistic-cultural aspect as the main factors that generated it. But they have not led to a unified conclusion. This study highlights the common elements of these theories, bringing together the two issues and providing a philosophical-religious interpretation.